ENHANCING GERMAN SPEAKING SKILLS THROUGH SHORT PODCASTS AND VIDEO CONTENT - Rakhmonkulova Dilshoda Murodkuziyevna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the effectiveness of short podcasts and video content in improving oral proficiency in the German language. With the rapid development of digital  technologies,  language  learners  increasingly  rely  on  multimedia  tools  to enhance  their  speaking  skills.  The  study  highlights  how  authentic  audio-visual materials  contribute  to  pronunciation,  vocabulary  acquisition,  listening comprehension, and confidence in communication. Practical strategies for integrating podcasts and videos into language learning routines are also discussed. The findings suggest that consistent exposure to short, engaging content significantly accelerates speaking fluency and interactive competence.